Tanz erben : Pina lädt ein - Wagenbach, Marc (Kultur- und Medientheorie., 2014)
»Inheriting Dance. An Invitation from Pina« sets out at the historical moment we found ourselves in after the passing of Pina Bausch. The Pina Bausch Foundation started their work of carrying the artistic heritage of dancer and choreographer Pina Bausch into the future. This book reflects discussions and questions aroused by her work: How to archive dance? How to deal with the performative heritage at the outset of the 21st century? How to describe the performativity of remembering? And finally, what is the task of an archive for tomorrow, an archive to serve as a workshop for the future? Furthermore, »Inheriting Dance« provides profound insight into the practical work of the Pina Bausch Foundation, on a local, national and global level, aiming at an archive as a place of transformation, exchange, creative production, and artistic practice, similar to an abundantly growing garden. A place for future generations of dancers, artists, non-professionals, and scholars. Contributions by Salomon Bausch, Stephan Brinkmann, Royd Climenhaga, Katharina Kelter, Gabriele Klein, Sharon Lehner, Keziah Claudine Nanevie, Linda Seljimi, Bernhard Thull, Michelle Urban and Marc Wagenbach.